Project implementation under donor and GOB fund: an analysis of "Construction of Server Stations for Electoral Database (CSSED)" project - Shiblee, Asheque Ahmed (BRAC University, 2014)
This dissertation report is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2013.